TESTING THREE STATISTICAL CRITERIA TO SCREENING S3 FAMILIES BY RECIPROCAL RECURRENT SELECTION IN POPCORN - & Jabouri, Mhomood (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
Afield experiment was conducted during in fall season 21 /7/2016 to screen  100 top crosses ,which is  represented   S3 generation, derived from  popcorn population AGR-2,  After one cycle of reciprocal recurrent selection (RRS). as The genotypes AGR-2 and Suror used  vtesters and evaluated with top crosses with control variexy. The experiment was carried out using 10x10 partial balance lattice design with two replications. Three statistical criteria for screening were used, First, standard error, the second duplicated standard error value and the third standard division value. All the values  statistical criteria were added to total mean. The results were  showed  a significant differences among in top crasses this study. Results of first criteria, were  included two groups, the first one consisted of 19 progenies,  was well of  performance  to  grain yield and popping expansion, second group was consisted of  10 progenies, which reveled well   expansion popping and  others  traits. The results of second criteria were  revealed  tow group, first one include10 progenies which had  the best of performance for grain yield and expansion popping while, another group include 8  progenies were well  performance of popping expansion. The third criteria which is  indicated  that  14 progenies were  best popping expansion and three progenies superior in   in grain yield per plant.